Detection of COX-2 in liquid biopsy in patients with breast cancer. Issue 12 (6th May 2020) - de Souza, Camilla Paulla; Alves, Beatriz; Waisberg, Jaques; Fonseca, Fernando; Carmo, Alipio de Oliveira; Gehrke, Flavia
Abstract : Aims: To determine the expression of the cyclooxygenase-2 ( COX-2 ) gene in patients with breast cancer attended at the Centro Universitário Saúde ABC/Faculdade de Medicina do ABC (CUS-ABC/FMABC) outpatient clinic. Breast cancer is the most common cancer in women worldwide. More than two million new cases are reported annually. An overexpression of COX-2 has been observed in many cancers. COX-2 is related to parameters of cancer aggressiveness, including tumour size, positive nodal state and lower survival, and to angiogenesis and resistance to apoptosis. Methods: 15 mL of peripheral blood was obtained from 34 patients and 21 healthy women. The extracellular RNA of QIAamp RNA was submitted to an RNA sequestration kit for RNA reverse transcriptase. Quantitative real-time PCR was performed using COX-2 -specific oligonucleotides and the endogenous Glyceraldehyde-3-Phosphate Dehydrogenase gene. Results: The mean remission time was 53 years. The mean progression time was 33 months. The difference observed between the patient and control groups in median COX-2 expression (p<0.001) was significant. Conclusions: Patients with breast cancer showed a higher mean COX-2 expression in peripheral blood samples at diagnosis than the control group. Since this information could prove important in the diagnosis and prognosis of breast cancer, further research is required on larger patient samples.